Critical Composition Today - Mahnkopf, Claus-Steffen (Hofheim Wolke Verlag, 2006)
Critical composition is generally associated with compositional approaches sharing a fundamental left-leaning political stance in relation to their own position in society that can lead to a decided political commitment, and is carried by the conviction that the treatment of musical material must be "critically" oriented. These positions have meanwhile gained astounding recognition, which must now in the face of the rapid societal changes since the late 1980s and also the "competing venture" of post-modernity, which seemingly denies the younger and middle generations access to a critical form of composition be problematized. More fundamentally, we must ask how a critical, socio-critical, and ideed politically sensitive mode of composition can be possible at all if it is not to lead to orthodoxy, stubbornness, or a narrow-mindedness; how, then, a cosmopolitan, universal and plural orientation that integrates the experience of the present is possible.In order to render the transition from a First to a Second Modernity comprehensible, essays have been requested from composers, musicologists, philosophers and sociologists. The contributors to the present volume are the following: Frank Cox, Gordon Downie, Ernst Helmuth Flammer, Harry Lehmann, Claus-Steffen Mahnkopf, Günter Mayer, Dieter Mersch, Rainer Nonnenmann, Nicola Sani, Gerhard Stäbler, and Ferdinand Zehentreiter.
Keywords: 21st Century (2001-2100); Music philosophy and esthetics; Composing; Politics